2018
DOI: 10.1103/physrevlett.120.188002
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries Control Collective Dynamics of Inertial Self-Propelled Robots

Abstract: Simple ingredients, such as well-defined interactions and couplings for the velocity and orientation of self-propelled objects, are sufficient to produce complex collective behavior in assemblies of such entities. Here, we use assemblies of rodlike robots made motile through self-vibration. When confined in circular arenas, dilute assemblies of these rods act as a gas. Increasing the surface fraction leads to a collective behavior near the boundaries: polar clusters emerge while, in the bulk, gaslike behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 44 publications
5
105
0
Order By: Relevance
“…Regarding the first situation, one of the best realization of our model equations (22) for active Langevin dynamics can be found for active granulates [13][14][15][16][17][18][19][20][21][22] . Typically these are hoppers with a Janus-like body or with tilted legs.…”
Section: A Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first situation, one of the best realization of our model equations (22) for active Langevin dynamics can be found for active granulates [13][14][15][16][17][18][19][20][21][22] . Typically these are hoppers with a Janus-like body or with tilted legs.…”
Section: A Generalmentioning
confidence: 99%
“…These motions are only virtually damped. Another important realization are granulates made self-propelling on a vibrating plate [13][14][15][16][17][18][19][20][21][22] or equipped with an internal vibration motor 23 where it has been shown that the active Langevin model indeed describes their dynamics well [24][25][26] . Further examples for self-propelled particles with inertia range from mini-robots 27,28 to macroscopic swimmers like beetles flying at water interfaces 29 and whirling fruits self-propelling in air 30 .…”
Section: Introductionmentioning
confidence: 99%
“…When the magnetic field is rapidly reversed, the MTB that are accumulated at the right of the NP and at the left of the SP can suddenly rotate to align along the new magnetic field, without any restriction from the droplet boundary. After this, they cross the droplet roughly along the y-direction, producing a transient convective circulation with positive values of Ω d (corresponding to CW direction) measured just after the magnetic field reversal (see Recently, considerable efforts have been undertaken to harness the microscopic activity of living or synthetic agents like bacteria [21,44], eukaryotic cells [45], Janus colloids [9] or micro-robots [46,47], in order to extract macroscopic work from microscopic mechanical structures. Here, we show a remarkable example of living biological entities self-assembling into a rotary motor actuated by a controlled, external aligning field.…”
Section: Vortex Reversalmentioning
confidence: 99%
“…As a matter of fact, a harmonic trap is not the only way to probe the self-alignment of the par-ticle: confining the particle with a hard wall of radius R w (in dimensionless units), an orbiting solution exists if τ n < R w , which slides along the wall at a velocity v = 1 − (τ n /R w ) 2 [18]. This suggests that the presence of such a coupling could be investigated in a num-ber of active systems, not only those using self-propelled particles similar to the present hexbugs [8,20], but also those in the colloidal realm, using for instance acoustic traps [6] or simply hard wall circular confinement.…”
mentioning
confidence: 99%